ANALYSIS OF THE INFLUENCE OF TRANSFER PRICING ON TAX AVOIDANCE IN MULTINATIONAL COMPANIES IN INDONESIA - Triasma, Citra; Faudah, Luk Luk (LP2M IBK Nitro, 2025)
This study analyzes the impact of transfer pricing practices on tax avoidance in Indonesian multinational companies through a literature review. This study examines various theoretical frameworks and empirical evidence to understand how multinational companies manipulate transfer pricing to shift profits to low-tax jurisdictions, thereby reducing their tax liabilities in Indonesia. This review synthesizes findings from existing studies, highlights challenges faced by Indonesian tax authorities in detecting and combating transfer pricing abuse, and proposes potential strategies to improve regulatory oversight and ensure fair tax collection.